Strategi BP3MI Kepri dalam Mengatasi Maraknya Pekerja Migran Non Prosedural - Rendy Syafutra; Sheila Yuni Artha Tamba; Sarah Cristiani (Indo Publishing, 2025)
The increasing number of cases of non-procedural migrant workers in the Riau Islands Province has become an increasing issue along with the high unemployment rate, limited employment opportunities, low quality of human resources (HR), and the large number of job opportunities and the lure of high salaries abroad. The geographical conditions of the Riau Islands which directly border neighboring countries also become a driving factor for the mobility of illegal workers through unofficial channels. This study aims to determine the strategy of the BP3MI Riau Islands in dealing with non-procedural migrant workers, especially in the case of worker placement in the online gambling industry in Cambodia. The method used is a descriptive qualitative approach with data collection techniques in the form of interviews, documentation, and observation. The results of the study indicate that the BP3MI Riau Islands strategy is implemented through an institutional approach consisting of: (1) Strong leadership through the implementation of pre-emptive, preventive, and repressive strategies; (2) Stakeholder commitment through coordination with local governments, security forces, immigration, port authorities, educational institutions, and the community; (3) Availability of resources to support the handling and repatriation of non-procedural PMI; and (4) Utilizing an effective information system through SAPA PMI and SISKO2 PMI to strengthen monitoring and protection services for migrant workers. This study concludes that the BP3MI Kepri strategy plays a significant role in suppressing illegal migration practices in the Riau Islands region, but further improvements in public education and supervision in border areas still need to be maximized.